(untitled) (Південний архів (історичні науки), 2026)
The aim of the article is to provide a comprehensive study of the transformation of the secondary education system in the Ternopil Voivodeship in 1932–1939 within the context of the implementation of the nationwide educational reform of the Second Polish Republic. In particular, it focuses on identifying structural, substantive, organizational, and personnel changes, as well as determining their impact on the development of the regional educational environment. Special attention is paid to the analysis of the introduction of the two-tier model of secondary education, the role of lyceums as a new type of educational institution, and the specific features of the functioning of state and private educational institutions in the multiethnic environment of the voivodeship. Research methods are based on a combination of general scientific and specialized historical approaches. The principles of historicism, objectivity, and systematicity have been applied, making it possible to consider educational processes within a broad socio-political context. The study employs methods of source analysis, comparative-historical, problem-chronological, and structuralfunctional approaches. The source base consists primarily of materials from educational periodicals, which made it possible to reconstruct both the regulatory foundations of the reforms and the practice of their implementation at the level of the Ternopil Voivodeship. The results of the study have shown that the transformation of the secondary education system in 1932–1939 was comprehensive and encompassed all key elements of the educational system. It has been established that the implementation of the Jędrzejewicz reform led to a transition from the eight-year gymnasium to a model consisting of a four-year gymnasium and a two-year lyceum, which ensured differentiation and specialization of education. In the region, there was an active expansion of the network of lyceums in district centers, contributing to broader access to secondary education. The modernization of the curriculum has been analyzed, particularly the introduction of applied subjects and the development of vocational education oriented toward labor market needs. Significant changes in teacher training have been identified, including the liquidation of teacher seminaries and the establishment of pedagogical lyceums. Particular attention is also given to the role of the private education sector and the specifics of national policy, manifested in the implementation of bilingualism (utrakwism) and the functioning of Ukrainian educational institutions under state supervision. Conclusions. The transformation of the secondary education system in the Ternopil Voivodeship in 1932–1939 was an integral part of the nationwide process of educational modernization and, at the same time, reflected regional socio-economic and national specificities. The reform contributed to the unification of the educational system, the improvement of the quality of student training, and the expansion of the functional capacities of secondary education, although it was accompanied by contradictory tendencies in the sphere of national policy. Overall, the educational transformations of this period laid the foundation for the formation of a new model of secondary education oriented toward combining general cultural training with the practical professionalization of youth.